Pengaruh Paparan Rokok Elektrik terhadap kadar GPx dan Catalase pada darah Tikus - Agustin, Mira Putri; Lisdiana, Lisdiana (Universitas Negeri Semarang, 2021)
Electric cigarettes are cigarettes that are used with battery power, but do not burn tobacco like ordinary cigarette products. Electric cigarettes were initially said to be safe for health because nicotine solutions contained in e-cigarettes only consist of a mixture of water, propylene glycol, flavor enhancing substances, the aroma of tobacco, and other compounds that do not contain tar, tobacco or other toxic substances common in tobacco cigarettes. Electric cigarettes contain free radical compounds that can cause oxidative stress. In conditions of oxidative stress, free radical compounds increase lipid peroxide. In normal enzyme activity, an increase in the concentration of substrate, namely the molecule hydrogen peroxide (H2O2) can increase enzyme activity. But when the active side of all enzymes binds to the substrate, the addition of the substrate cannot increase the speed of the next enzyme reaction, resulting in a decrease in enzyme activity. This study aimed to analyze the levels of GPx and catalase in rat blood exposed to electrocution cigarettes. The study was conducted on 30 male white rats of Wistar strain which were divided into 5 groups, namely K- (negative control), K + (positive control), KP1 (treatment 1), KP2 (treatment 2) and KP3 (treatment 3). The K + group is a positive control group with 3 cigarettes and KP1, KP2, KP3 electric cigarette treatment groups treated with e-cigarettes with a dose of nicotine 3 mg, 6 mg, 9 mg for 30 days. To find out the difference in GPx and catalase levels, each group was analyzed by using one way annova and LSD for parametric test, while for non-parametric tests using the kruskal wallis test and Mann Whitney test. The results of the analysis showed that all between groups K-, K +, KP1, KP2 and KP3 were significantly different, in the KP3 group had the level of Gpx (40.25 ± 2.03e) and catalase (2.46 ± 9.50e) which was the lowest due to exposure electric cigarette with the highest dose of nicotine which is 9 mg. Keywords: Electric cigarettes, GPx, catalase, Rokok elektrik, GPx, katalase Rokok elektrik adalah rokok yang digunakan dengan tenaga baterai, namun tidak membakar tembakau seperti produk rokok biasa. Rokok elektrik pada awalnya dikatakan aman bagi kesehatan karena larutan nikotin yang terdapat pada rokok elektrik hanya terdiri dari campuran air, propilen glikol, zat penambah rasa, aroma tembakau, serta senyawa-senyawa lain yang tidak mengandung tar, tembakau atau zat-zat toksik lain yang umum terdapat pada rokok tembakau. Rokok elektrik mengandung senyawa radikal bebas yang dapat menyebabkan stress oksidatif. Pada kondisi stress oksidatif, senyawa radikal bebas meningkatkan peroksida lipid. Dalam aktivitas enzim yang normal, peningkatan konsentrasi subtrat, yaitu molekul hidrogen peroksida (H2O2) dapat meningkatkan aktivitas enzim. Namun pada saat sisi aktif semua enzim berikatan dengan substrat, penambahan substrat tidak dapat meningkatkan kecepatan reaksi enzim selanjutnya, sehingga terjadi penurunan aktivitas enzim. Penelitian ini bertujuan untuk menganalisis kadar GPx dan katalase pada darah tikus yang dipapar rokok elktrik. Penelitian dilakukan pada 30 ekor tikus putih jantan galur Wistar yang dibagi menjadi 5 kelompok, yaitu K- (kontrol negatif), K+ (kontrol positif), KP1 (perlakuan 1), KP2 (perlakuan 2) dan KP3 (perlakukan 3). Kelompok K+ merupakan kelompok kontrol positif dengan perlakuan rokok elektrik 3 batang dan kelompok KP1, KP2, KP3 merupakan kelompok perlakukan dengan rokok elektrik dosis nikotin 3 mg, 6 mg, 9 mg selama 30 hari. Untuk mengetahui perbedaan kadar GPx dan katalase setiap kelompok dilakukan analalisis data menggunakan uji one way annova dan LSD untuk parametrik sedangkan untuk non parametrik menggunakan uji kruskal wallis dan uji mann whitney. Hasil analisis menunjukkan semua antar kelompok K-, K+, KP1, KP2 dan KP3 berbeda nyata, pada kelompok KP3 memiliki kadar Gpx (40,25 ± 2,03e) dan katalase (2,46 ± 9,50e) yang paling rendah akibat dipapar rokok elektrik dengan dosis nikotin paling tinggi yaitu 9 mg. Keywords: Electric cigarettes, GPx, catalase, Rokok elektrik, GPx, katalase